2020
DOI: 10.1155/2020/4637043
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Utility of Plasma NGAL Levels in ST Segment Elevation in Myocardial Infarction Patients

Abstract: Introduction. Plasma neutrophil gelatinase-associated lipocalin (NGAL) levels in acute myocardial infarction (AMI) patients are markedly higher. In addition, plasma NGAL levels were increased in patients with acute and chronic heart failure as a complication of myocardial infarction. In this study, we investigated whether there is a difference between the prognostic use of plasma NGAL levels in ST-elevation myocardial infarction (STEMI) patients with preserved and reduced left ventricular ejection fraction (LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…Plasma NGAL levels were markedly higher in death patients with STEMI than survivors. The ROC curve analysis showed that NGAL of more than 190 ng/mL could detect cardiovascular mortality in STMI patients with a sensitivity of 86% and specificity of 77% [ 86 ]. Among 260 STEMI patients admitted within 24 h after onsetting clinical symptoms, plasm NGAL on day 12 could predict combined adverse outcomes, including recurrent myocardial infarction, post-infarction angina, acute cerebrovascular accident, and death [ 87 ].…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma NGAL levels were markedly higher in death patients with STEMI than survivors. The ROC curve analysis showed that NGAL of more than 190 ng/mL could detect cardiovascular mortality in STMI patients with a sensitivity of 86% and specificity of 77% [ 86 ]. Among 260 STEMI patients admitted within 24 h after onsetting clinical symptoms, plasm NGAL on day 12 could predict combined adverse outcomes, including recurrent myocardial infarction, post-infarction angina, acute cerebrovascular accident, and death [ 87 ].…”
Section: Neutrophil Gelatinase-associated Lipocalin (Ngal)mentioning
confidence: 99%
“…Plasma NGAL levels were markedly higher in death patients with STEMI than survivors 2. Plasma NGAL levels were increased in patients with acute and chronic heart failure as a complication of MI [ 86 ] NGAL prognosis value MI patients Higher baseline NGAL and a more significant increase in serum NGAL level were correlated with lower 6-month LV ejection fraction recovery [ 76 ] AMI patients 1. Plasma NGAL level was significantly higher in death patients than in survived patients of AMI 2.…”
Section: Arginasementioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed the proportion of female patients was 51.7%, and the mean age was 67.48 ± 11.63. The patient's baseline characteristics were mostly similar in mean age, and difference in sex proportion [5] , [6] , [15] , [16] , [17] , [18] . Sex proportion was major sex was male from the study of Adnan Burak Akcay (2016) [6] , Katerina Helanova (2015) [5] , Peng-Ju Lu (2020) [15] , David Zahler (2022) [16] , Ahmet Avci (2020) [17] , and Alan S. Maisel (2011) [18] .…”
Section: Discussionmentioning
confidence: 93%
“…The patient's baseline characteristics were mostly similar in mean age, and difference in sex proportion [5] , [6] , [15] , [16] , [17] , [18] . Sex proportion was major sex was male from the study of Adnan Burak Akcay (2016) [6] , Katerina Helanova (2015) [5] , Peng-Ju Lu (2020) [15] , David Zahler (2022) [16] , Ahmet Avci (2020) [17] , and Alan S. Maisel (2011) [18] . Medical history of hypertension (70.7%); smoking (41.4%); lipid abnormalities (79.3%); and type 2 diabetes (24.1%).…”
Section: Discussionmentioning
confidence: 93%